Earthquake or glacier? How CEO charisma manifests in firm strategy over time - Wowak, Adam J.; Mannor, Michael J.; Arrfelt, Mathias; McNamara, Gerry (Strategic Management Journal, 2016)
Numerous studies have focused on CEO charisma as an antecedent to firm performance, but this literature has largely overlooked the possibility that charisma manifests in more proximal strategic initiatives that (unlike performance) are largely under the CEO 's control. In this study, we integrate perspectives from the upper echelons and charismatic leadership literatures to argue that CEO charisma influences year‐over‐year strategic change, the degree to which strategies deviate from industry central tendencies, and the degree of emphasis on corporate social responsibility. We also theorize that, depending on the outcome in question, the effects of charisma can become both amplified and diminished as CEO tenure advances. Employing a novel data collection approach for a sample of 113 S&P 500 CEOs , we find broad support for our theory. Copyright © 2014 John Wiley & Sons, Ltd .